Crispr/Cas9-Mediated Disruption of the pcz1 Gene and Its Impact on Growth, Development, and Penicillin Production in Penicillium Rubens - Levican-Jaque, G; Martinez-Fernandez, C; Palacios-Pino, J; Chavez-Rosales, R; Gil-Duran, C; Rojas-Aedo, J (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Penicillium rubens is a filamentous fungus of great biotechnological importance due to its role as an industrial producer of the antibiotic penicillin. However, despite its significance, our understanding of the regulatory mechanisms governing biological processes in this fungus is still limited. In fungi, zinc finger proteins containing a Zn(II)2Cys6 domain are particularly interesting regulators. Although the P. rubens genome harbors many genes encoding proteins with this domain, only two of them have been investigated thus far. In this study, we employed CRISPR-Cas9 technology to disrupt the pcz1 gene, which encodes a Zn(II)2Cys6 protein in P. rubens. The disruption of pcz1 resulted in a decrease in the production of penicillin in P. rubens. This decrease in penicillin production was accompanied by the downregulation of the expression of pcbAB, pcbC and penDE genes, which form the biosynthetic gene cluster responsible for penicillin production. Moreover, the disruption of pcz1 also impacts on asexual development, leading to decreased growth and conidiation, as well as enhanced conidial germination. Collectively, our results indicate that pcz1 acts as a positive regulator of penicillin production, growth, and conidiation, while functioning as a negative regulator of conidial germination in P. rubens. To the best of our knowledge, this is the first report involving a gene encoding a Zn(II)2Cys6 protein in the regulation of penicillin biosynthesis in P. rubens. © 2023 by the authors.